Iron oxide thin film, and methods for producing the same
Patent Information
- Application Number
- JP2024152341
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-09-04
- Filing Date
- 2024-09-04
- Publication Date
- 2025-03-14
AI Technical Summary
【0016】 Si、ZrおよびMnの群からなる少なくとも1種の元素が所定の量添加された、本発明に係る鉄酸化物によれば、磁化の向上が図られる。また、熱処理を施すことがないので、経済的および時間的な観点から製造コストを低減することができる。
Smart Images

Figure 2025036403000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to an iron oxide thin film and a method for producing the same. [Background technology]
[0002] As iron oxide oxidizes, it turns into wustite (Fe 1-x O) to magnetite (Fe3O4), maghemite (γ-Fe2O3), and finally hematite (α-Fe2O3), which exhibit semimetallic, ferrimagnetic, and semiconducting properties. Fe3O4 has Fe in the octahedral B sites. 2+ and Fe in both the tetrahedral A site and the octahedral B site. 3+ This situation occurs when the electrons move from Fe to Fe at temperatures above 120 K. 2+ and Fe 3+ Since the temperature transition occurs between 0 and 850 K (Verwey transition), the electrical resistivity is relatively low (see, for example, Non-Patent Document 1), and the ferrimagnetic behavior exists up to 850 K (see, for example, Non-Patent Document 2). These properties have potential applications in spintronics devices (see, for example, Non-Patent Document 3), gas sensors (see, for example, Non-Patent Document 4), resistive random access memories (see, for example, Non-Patent Document 5), and the like.
[0003] In order to maintain the performance of devices or elements containing Fe3O4 and to expand their use in other applications, it is necessary to increase the transition temperature of Fe3O4. The phase transition of powdered Fe3O4 depends on the heat treatment temperature and the crystal size (see, for example, Non-Patent Documents 6-17), and when the temperature exceeds 493K, crystals with a size of 300 nm or less change to γ-Fe2O3 (see, for example, Non-Patent Document 11). This occurs because the activation energy of the phase transition decreases as the particle size decreases (see, for example, Non-Patent Document 14). When at least one of Mn, Co, Ni, Zn, Cu, Al, V, and is added, the transition temperature increases from 773K to 923K. Alternative technologies for iron oxide nanoparticles have been proposed, such as forming a core-shell structure with a shell of SnO2 (see, for example, Non-Patent Document 18) and phosphate carbon material (see, for example, Non-Patent Document 19) to protect the Fe3O4 core from oxidation. When formed as a thin film, undoped Fe3O4 undergoes a phase transition to γ-Fe2O3 in air at temperatures between 573 K and 603 K (see, for example, Non-Patent Document 20), but it is unclear how to impart oxidation resistance to metal-doped Fe3O4 thin films.
[0004] In addition to the fabrication of single-phase Fe3O4 films using radio frequency (RF) sputtering with a metal tip on an Fe3O4 target, ceramic Fe3O4 targets without metal tips have been reported to produce a mixture of Fe3O4 and α-Fe2O3 phases (see, for example, Patent Document 1 and Non-Patent Documents 21 and 22). Furthermore, it has been found that the magnetization of Fe3O4 thin films is maximized at relatively low metal concentrations.
[0005] The present inventors have also disclosed a composite iron oxide thin film having improved oxidation resistance and a method for producing the same, in which one or more elements selected from the group consisting of Mo, W, and Mg are added to the maghemite crystal phase, or Ge is added to the magnetite crystal phase, providing a magnetic material with oxidation resistance (Patent Document 2). [Prior art documents]
Chartered Documents
[0006] [Patent Document 1] Patent No. 5389370 [Patent Document 2] Patent No. 7153555
Non-licensed documents
[0007]
Non-patent document 1
Non-patent document 2
Non-patent document 3
Non-patent document 4
Non-patent document 5
Non-patent document 6
Non-patent document 7
Non-patent document 8
Non-licensed literature 9
Non-licensed literature 10
Non-licensed Document 11
Non-licensed Document 12
Non-licensed Document 13
Non-licensed Document 14
Non-licensed Document 15
Non-licensed Document 16
Non-licensed Document 17
Non-licensed Document 18
Non-licensed Document 19
Non-licensed Document 20
Non-licensed Document 21
Non-licensed Document 22
Non-licensed Document 23
Non-licensed Document 24
Non-licensed Document 25
[0008] The iron oxides disclosed in Patent Documents 1 and 2 improve magnetization, but have the problem that the magnetite is subjected to heat treatment, which requires many complicated processes, and the cost increases due to economic and time constraints. The present invention has been made in view of the above problems, and aims to provide an iron oxide thin film that improves magnetization without complicated processes, and a method for producing the same. [Means for solving the problem]
[0009] In order to solve the above problems, the iron oxide thin film and the method for producing an iron oxide thin film of the present invention are characterized by having the following invention-specifying features.
[0010] The iron oxide thin film of the present invention is Composition formula Fe 1-a-b S a O b(However, 0 < a ≤ 0.1, 0.48 ≤ b ≤ 0.61, and 0.32 ≤ 1 - (a + b) ≤ 0.43), and is composed of a magnetite crystal phase.)
[0011] The iron oxide thin film of the present invention is Composition formula Fe 1-a-b Zr a O b (However, 0 < a ≤ 0.1, 0.48 ≤ b ≤ 0.61, and 0.32 ≤ 1 - (a + b) ≤ 0.43), and is composed of a magnetite crystal phase.)
[0012] The iron oxide thin film of the present invention is Composition formula Fe 1-a-b Mn a O b (However, 0 < a ≤ 0.22, 0.48 ≤ b ≤ 0.61, and 0.32 ≤ 1 - (a + b) ≤ 0.43), and is composed of a magnetite crystal phase.)
[0013] The manufacturing method of the iron oxide thin film of the present invention is Using a composite target with Si chips arranged on an Fe3O4 target as the target material, by high-frequency sputtering method, a composition formula Fe 1-a-b Si a O b (However, 0 < a ≤ 0.7, 0.48 ≤ b ≤ 0.61, and 0.32 ≤ 1 - (a + b) ≤ 0.43), and includes the step of producing an iron oxide thin film composed of a magnetite crystal phase.)
[0014] The manufacturing method of the iron oxide thin film of the present invention is Using a composite target with Zr chips arranged on an Fe3O4 target as the target material, by high-frequency sputtering method, a composition formula Fe 1-a-b Zr a O b (However, 0 < a ≤ 0.7, 0.48 ≤ b ≤ 0.61, and 0.32 ≤ 1 - (a + b) ≤ 0.43), and includes the step of producing an iron oxide thin film composed of a magnetite crystal phase.)
[0015] The method for manufacturing an iron oxide thin film of the present invention includes a step of producing an iron oxide thin film represented by the composition formula Fe using a composite target in which Mn chips are arranged on a Fe3O4 target as a target material, and by high-frequency sputtering, 1-a-b Mn a O b (where 0 < a ≤ 0.22, 0.48 ≤ b ≤ 0.61, and 0.32 ≤ 1 - (a + b) ≤ 0.43), and composed of a magnetite crystal phase.
Advantages of the Invention
[0016] According to the iron oxide of the present invention, to which at least one element selected from the group consisting of Si, Zr, and Mn is added in a predetermined amount, the magnetization can be improved. Further, since no heat treatment is performed, the manufacturing cost can be reduced from the economic and time viewpoints.
Brief Description of the Drawings
[0017] [Figure 1] Three-component phase diagram of the iron oxide thin film according to the present invention. [Figure 2A] Explanatory diagram regarding the correlation between the Si addition amount and the X-ray diffraction pattern of the iron oxide thin film before heat treatment. [Figure 2B] Explanatory diagram regarding the correlation between the Si addition amount and the magnetization curve of the iron oxide thin film before heat treatment. [Figure 3A] Diagram showing the change in magnetization at 10 kOe with respect to the Si addition amount of the iron oxide thin film before heat treatment. [Figure 3B] Diagram showing the change in magnetization at 10 kOe with respect to the Si, Zr, and Mn addition amounts of the iron oxide thin film before heat treatment. [Figure 3C] Diagram showing the XPS spectrum of the iron oxide thin film when the Si addition amount is 2.8 [at.%] before heat treatment.
Embodiments for Carrying Out the Invention
[0018] (Configuration) The iron oxide thin film as one embodiment of the present invention has a composition formula Fe 1-a-b L a O b (where L is at least one element selected from Si, Mn, and Zr), and has a structure composed of a magnetite crystal phase. Here, when L is Si, 0 < a ≤ 0.1, 0.48 ≤ b ≤ 0.61, and 0.32 ≤ 1 - (a + b) ≤ 0.43; when L is Zr, 0 < a ≤ 0.1, 0.48 ≤ b ≤ 0.61, and 0.32 ≤ 1 - (a + b) ≤ 0.43; when L is Mn, 0 < a ≤ 0.22, 0.48 ≤ b ≤ 0.61, and 0.32 ≤ 1 - (a + b) ≤ 0.43.
[0019] The values of a and b of the iron oxide thin film when L is Si are not limited to the above values. The value of a is preferably 0.001 to 0.1, more preferably 0.005 to 0.05, and still more preferably 0.005 to 0.03. b is preferably 0.57 to 0.61, more preferably 0.58 to 0.605, and still more preferably 0.59 to 0.605.
[0020] The values of a and b of the iron oxide thin film when L is Zr are not limited to the above values. The value of a is preferably 0.001 to 0.1, more preferably 0.005 to 0.05, and still more preferably 0.005 to 0.03. b is preferably 0.57 to 0.61, more preferably 0.58 to 0.605, and still more preferably 0.59 to 0.605.
[0021] The values of a and b of the iron oxide thin film when L is Mn are not limited to the above values. The value of a is preferably 0.08 to 0.17, more preferably 0.08 to 0.1, and still more preferably 0.085 to 0.095. b is preferably 0.57 to 0.61, more preferably 0.58 to 0.605, and still more preferably 0.59 to 0.605.
[0022] Furthermore, when the iron oxide thin film contains a combination of at least two elements selected from the group consisting of Si, Mn, and Zr, the total content of these elements is preferably 0.1 to 10 at.%, more preferably 0.5 to 5 at.%, and even more preferably 0.5 to 3 at.%.
[0023] The iron oxide thin film according to the present invention has a saturation magnetization of preferably 1 kG or more, more preferably 3 kG or more, even more preferably 4 kG or more, and most preferably 4.5 kG or more. There is no particular upper limit for the saturation magnetization, but it may be 100 kG depending on the characteristics of the material.
[0024] (Manufacturing method) A composite target in which chips of at least one element selected from the group consisting of Si, Mn, and Zr are arranged on a magnetite (Fe3O4) target is placed in a thin film manufacturing device (such as a sputtering device). The concentration of at least one element selected from the group consisting of Si, Mn, and Zr is preferably a concentration that maximizes the magnetization of the element-added Fe3O4 thin film, for example, 1.8 at.% in the case of Si (see, for example, Non-Patent Documents 21 and 22). After that, a substrate such as a Corning #7059 glass substrate is sputter-etched for an appropriate time, and then an AC voltage is applied to the target to form an Fe3O4 thin film to which the metal has been added in an atmosphere such as Ar gas (see, for example, Patent Document 1 and Non-Patent Document 21). In this way, a thin film of Fe3O4 having the composition formula Fe 1-a-b L a O b (wherein L is at least one element selected from the group consisting of Si, Mn, and Zr), and an iron oxide morphology consisting of a magnetite crystal phase is created. At this time, the thin film is created without performing any special treatment such as applying a bias voltage near the substrate. EXAMPLES
[0025] First, we will explain the composite iron oxide thin film containing Si as an additive element.
[0026] Two 5 mm square Si chips were attached to the surface of a 4-inch magnetite target using double-sided carbon tape, and the target was placed in the vacuum chamber of a high-frequency sputtering device. A plate glass (manufactured by Corning) was placed in the vacuum chamber as a substrate. Next, the vacuum chamber was filled with 1.5 × 10 -7 The chamber was evacuated to a vacuum of 100 Torr, and then argon gas was supplied into the vacuum chamber to control the gas pressure to 2 mTorr while depositing the film for 60 minutes at a power input of 200 W, thereby producing the iron oxide thin film of Example 1 having a thickness of 1 μm. Analysis of the composition of the iron oxide thin film of Example 1 revealed that the amount of Si added was 2.8 at.%.
[0027] (Examples 2 to 6) Except for varying the number (or size) of Si chips attached to the surface of the magnetite target, the iron oxide thin films of Examples 2 to 6 were produced in the same manner as in Example 1. When the composition of each of the iron oxide thin films of Examples 2 to 6 was analyzed, the amount of Si added was identified as shown in Table 1.
[0028] (Comparative Example) Except for changing the chip attached to the surface of the magnetite target from Si to Mo, the iron oxide thin films of Comparative Examples 1 and 2 were produced in the same manner as in Example 1. When the composition of each of the iron oxide thin films of Comparative Examples 1 and 2 was analyzed, the amounts of addition were identified as shown in Table 1.
[0029] Table 1 shows the compositions of the iron oxide thin films of Examples 1-6 and Comparative Examples 1-2.
[0030] [Table 1]
[0031] To avoid redundancy, a description of the manufacturing method will be omitted. However, for composite iron oxide thin films to which at least one element other than Si, selected from the group consisting of Mn and Zr, was added, examples corresponding to a plurality of different amounts of addition were produced by a similar manufacturing method.
[0032] (Thin film evaluation method) The magnetization of the thin films at room temperature was measured using a vibrating sample magnetometer (Tamagawa Seisakusho). The optical properties (optical transmittance) of the thin films were measured using a UV-Vis-Infrared Spectrophotometer (Shimadzu Seisakusho). The structure of the thin films was identified using X-ray diffraction (XRD) using CuKα radiation (Rigaku). The constituent elements of the thin films and the electronic state of the elements were identified using X-ray photoelectron spectroscopy (XPS) (PHI) using a monochromated Al X-ray source. The films were observed using a scanning transmission electron microscope (STEM), high-angle annular dark-field (HAADF) STEM, and energy dispersive X-ray spectroscopy (EDX) (JEOL Ltd.) operating at 200 kV for elemental analysis of Si-K, Fe-K, and OK. Samples for cross-sectional imaging were prepared using a focused ion beam.
[0033] (Characteristics of thin iron oxide films) In FIG. 1, square points corresponding to the compositions of Fe3O4 and SiFe2O4 are shown. In FIG. 1, the composition analysis results of the Si-added iron oxide thin film in the formed state are shown by black circles. In FIG. 1, the dashed line represents the composition (Si+Fe2O3) assuming that Si and Fe3O4 are phase-separated. The dashed line represents the composition (the line connecting the square points of Fe3O4 and SiFe2O4) assuming that Si and Fe3O4 are in solid solution. The analysis results change along the line assuming a solid solution rather than the line assuming phase separation, suggesting that the added Si is in solid solution in Fe3O4. In addition, the amount of Si added to the iron oxide thin film is set to 0.1 or less (10 at.%) in atomic ratio because the structure changes rapidly when the amount of Si added exceeds this amount, making it difficult for Si to be solid-soluble in magnetite, resulting in amorphous formation.
[0034] Although the explanation is omitted to avoid redundancy, the analysis results are similar for Zr and Mn, and it is preferable to adjust the amount of addition from the viewpoint of dissolving the added element in Fe3O4. From the viewpoint of reliably dissolving the added element in magnetite, when the added element in the solid-dissolved iron oxide thin film is Zr, the added amount is preferably 0.1 or less (10 at.% or less) in atomic ratio, and when the added element in the solid-dissolved iron oxide thin film is Mn, the added amount is preferably 0.22 or less (22 at.% or less) in atomic ratio. If the added amount is exceeded, the structure changes rapidly, making it difficult for the element to dissolve in magnetite, resulting in amorphous formation.
[0035] Figure 2A shows the correlation between the amount of Si added and the X-ray diffraction pattern of the iron oxide thin film. When the amount of Si added is 0 [at.%] (x = 0), a small peak is observed at Miller index (104) corresponding to the corundum structure. When the amount of Si added is 0.7 [at.%] (x = 0.049) or more, no peak corresponding to the corundum structure is observed, and only peaks at Miller indexes (311), (222), (422), and (511) corresponding to the inverse spinel structure specific to magnetite are observed. When the amount of Si added is 7.8 [at.%] (x = 0.546), no peak corresponding to the inverse spinel structure is observed. That is, when the amount of Si added is 0 [at.%] (x = 0), a mixed phase of magnetite and hematite is formed, when even a small amount of Si is added, a single phase of magnetite is formed, and when the amount of Si added exceeds a certain value, an amorphous phase is formed.
[0036] FIG. 2B shows the magnetization-magnetic field curves of the Si addition amount and the iron oxide thin film. When the Si addition amount was 0 [at.%] and when the Si addition amount was 2.8 [at.%], the first iron oxide layer X1 exhibited ferrimagnetic behavior. When the Si addition amount was 2.8 [at.%], the ferrimagnetic behavior of the iron oxide thin film was such that the saturation magnetization increased compared to when the Si addition amount was 0 [at.%], indicating that by adding Si, magnetite was formed as a single phase and high magnetization was obtained (saturation magnetization increased from less than 4 kG to 4 kG or more). On the other hand, when the Si addition amount exceeded a certain value, amorphous phase was formed, and the ferrimagnetic behavior was no longer exhibited.
[0037] FIG. 3A shows the magnetization at 10 kOe as a function of the amount of Si added to the iron oxide thin film. FIG. 3B shows the change in magnetization at 10 kOe with respect to the amount of Si, Zr, and Mn added to the iron oxide thin film before heat treatment. Referring to FIG. 3A and FIG. 3B, in the relatively low concentration region, the magnetization of the iron oxide shows a tendency to increase with increasing amounts of Si, Zr, and Mn added, but when the amount of Si, Zr, and Mn added exceeds a certain value, it decreases rapidly, and thereafter the magnetization has a low value. From this, it is clear that the magnetization is increased by adding a certain amount of Si, Zr, and Mn compared to Fe3O4 without addition. Here, the mixture of hematite and magnetite in the initial state is different between the disk A and the disk B, which are the sputtering targets. Therefore, it is presumed that the values of the curves in disk A and disk B in FIG. 3A are different. On the other hand, in disk B, the magnetization was maximized when the Si addition amount was 1.8 at.%, suggesting that the magnetization is maximized when the Si addition amount is around 1.8 at.%.
[0038] Here, the predetermined amount is preferably 0.5 to 3.5 [at.%], more preferably 0.5 to 2.5 [at.%], and even more preferably 1.5 to 2.5 [at.%] when the additive element is Si. Also, when the additive element is Zr, the predetermined amount is preferably 0.5 to 3.5 [at.%], more preferably 1.2 to 3.2 [at.%], and even more preferably 1.7 to 2.7 [at.%]. Also, when the additive element is Mn, the predetermined amount is preferably 7.5 to 10.5 [at.%], more preferably 8.0 to 10 [at.%], and even more preferably 8.5 to 9.5 [at.%].
[0039] By setting the amount of the additive element to the above value, the additive element can be reliably dissolved in Fe3O4 and the magnetization can be increased. If the amount of the additive element is less than the above value or if no additive element is added, the magnetization does not become larger than necessary, but if the amount of the additive element is more than the above value, the additive element is less likely to be dissolved in magnetite, or the crystallinity is deteriorated or the element is easily made amorphous, or the element is transferred to a solid solution that is not magnetized, and the magnetization is reduced.
[0040] The magnetization at 10 kOe of the iron oxide thin film containing 1.3 at.% Mo shown in Comparative Example 2 (iron oxide thin film containing such a Mo content that the magnetization at 10 kOe is maximum) was 3.2 kG. Referring to Figs. 3A and 3B, it was clear that the magnetization at 10 kOe of the iron oxide containing the above-mentioned predetermined amount was at least 3.4 kG or more, and the magnetization at 10 kOe was larger than that of Comparative Example 2. Referring to Fig. 3A, the magnetization at 10 kOe of the additive-free iron oxide thin film was 3.6 kG (Comparative Example 1) for disk A and 0.7 kG for disk B. This is because the quality of the ceramic disks used in sputtering was different.
[0041] The reason why the magnetization increased by adding Si, Mn, and Zr is that, while unmagnetized hematite inevitably gets mixed in without any additives and reduces the magnetization of the thin film, by adding a certain amount of Si, Mn, Zr, etc., the hematite disappears and becomes a single phase of ferromagnetic magnetite, and the magnetite crystal grains become larger and the spin direction becomes easier to align. Also, the reason why the magnetization of the unadded disk in Figure 3A is lower in disk B than disk A is because the amount of hematite mixed in is greater in disk B than disk A.
[0042] Figure 3C shows the XPS spectrum of the iron oxide thin film with 2.8 at.% Si added. The peak of the XPS spectrum is between the trivalent and tetravalent Si, suggesting that the Si added to the iron oxide thin film is ionized and dissolved in magnetite. This result is in good agreement with the tendency of the analysis results (Figure 1) in the as-formed film.
[0043] To avoid redundancy, a detailed explanation of the structure of iron oxide thin films containing elements other than Si will be omitted. However, it was suggested that similar structural characteristics (XPS spectra) were observed in iron oxide thin films containing elements other than Si, such as Mn and / or Zr.
[0044] Therefore, the iron oxide thin film of the present invention provides a magnetic material with improved magnetization without the need for heat treatment, and therefore the manufacturing costs can be reduced from the economic and time standpoints.
Claims
【Request 1】 Composition formula Fe 1-a-b S a O b (wherein 0<a≦0.1, 0.48≦b≦0.61, and 0.32≦1−(a+b)≦0.43) and the thin iron oxide film is constituted by a magnetite crystal phase. 【Request 2】 Composition formula Fe 1-a-b Zr a O b (wherein 0<a≦0.1, 0.48≦b≦0.61, and 0.32≦1−(a+b)≦0.43) and the thin iron oxide film is constituted by a magnetite crystal phase. 【Request 3】 Composition formula Fe 1-a-b Mn a O b (wherein 0<a≦0.22, 0.48≦b≦0.61, and 0.32≦1−(a+b)≦0.43) and the thin iron oxide film is constituted by a magnetite crystal phase. 【Request 4】 Fe as the target material 3 O 4 A composite target with Si chips placed on the target was used to deposit Fe with the composition formula Fe1, Fe2, Fe3, Fe4, Fe5, Fe6, Fe7, Fe8, Fe9, Fe10, Fe11, Fe12, Fe13, Fe14, Fe15, Fe16, Fe17, Fe18, Fe19, Fe20, Fe15, Fe21, Fe16, Fe18, Fe22, Fe15, Fe16, Fe17, Fe23, 1-a-b S a O b (wherein 0<a≦0.1, 0.48≦b≦0.61, and 0.32≦1-(a+b)≦0.43) and the method for producing an iron oxide thin film is comprised of a magnetite crystal phase. 【Request 5】 Fe as the target material 3 O 4 A composite target with Zr chips placed on the target was used for radio frequency sputtering to produce a compound with the formula Fe 1-a-b Zr a O b (wherein 0<a≦0.1, 0.48≦b≦0.61, and 0.32≦1-(a+b)≦0.43) and the method for producing an iron oxide thin film is comprised of a magnetite crystal phase. [Request 6] Fe as the target material 3 O 4 A composite target with Mn chips placed on the target was used to deposit Fe with the composition formula Fe1, Fe2, Fe3, Fe4, Fe5, Fe6, Fe7, Fe8, Fe9, Fe10, Fe11, Fe12, Fe13, Fe14, Fe15, Fe16, Fe17, Fe18, Fe19, Fe20, Fe15, Fe21, Fe16, Fe18, Fe15, Fe22, Fe15, Fe16, Fe17 1-a-b Mn a O b (wherein 0<a≦0.22, 0.48≦b≦0.61, and 0.32≦1-(a+b)≦0.43) and the method for producing an iron oxide thin film is comprised of a magnetite crystal phase.
Citation Information
Patent Citations
Roll electrode for hermetic sealing of semiconductor device
JP1978089370A
Composite iron oxide thin film and method for producing the same
JP7153555B2